Pertunjukan Amal: Dana Awal Perjuangan Rakyat di Yogyakarta 1945-1947 - Ihza Arvianita; Yuli Eko Basuki (Lembaran Sejarah, 2022)
This research discusses the existence of charity shows in Yogyakarta as one of the people’s efforts to support the financial needs of independence struggle bodies. As the capital of the revolution, Yogyakarta’s atmosphere was filled with patriotic spirit to defend independence, and its society supported the birth of struggle organizations. To finance their activities, people conducted fundraising activities, such as by organizing charity shows. This method was chosen because of its effectiveness in mobilizing charity-fund from society, since at the same time they also enjoyed entertainment. The shows were presented in the form of theater and cinema. From these charity shows, the collected funds were distributed to various independence struggle bodies such as People’s Militia, Independence Funds Agency, and the Indonesian Red Cross (PMI).